(untitled) (Journal of the College of Basic Education, 2022)
This study aimed to find out the impact of teaching using systemic thinking skills in the direction towards mathematics among female students in the fourth scientific grade. The study sample consisted of (54) students distributed into two equal divisions. According to the usual method, the attitude towards mathematics scale was built along the lines of the three-point Likert scale, and it consisted of (30 items). Its validity and reliability were verified. The t-test formula was used for two independent samples to process the data. Significance level (0.05)